Ongoing Exercise Intolerance Following COVID‐19: A Magnetic Resonance–Augmented Cardiopulmonary Exercise Test Study - James T. Brown; Anita Saigal; Nina Karia; Rishi K. Patel; Yousuf Razvi; Natalie Constantinou; Jennifer A. Steeden; Swapna Mandal; Tushar Kotecha; Marianna Fontana; James Goldring; Vivek Muthurangu; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Ongoing exercise intolerance of unclear cause following COVID‐19 infection is well recognized but poorly understood. We investigated exercise capacity in patients previously hospitalized with COVID‐19 with and without self‐reported exercise intolerance using magnetic resonance–augmented cardiopulmonary exercise testing. Methods and Results Sixty subjects were enrolled in this single‐center prospective observational case‐control study, split into 3 equally sized groups: 2 groups of age‐, sex‐, and comorbidity‐matched previously hospitalized patients following COVID‐19 without clearly identifiable postviral complications and with either self‐reported reduced (COVIDreduced) or fully recovered (COVIDnormal) exercise capacity; a group of age‐ and sex‐matched healthy controls. The COVIDreducedgroup had the lowest peak workload (79W [Interquartile range (IQR), 65–100] versus controls 104W [IQR, 86–148]; P=0.01) and shortest exercise duration (13.3±2.8 minutes versus controls 16.6±3.5 minutes; P=0.008), with no differences in these parameters between COVIDnormal patients and controls. The COVIDreduced group had: (1) the lowest peak indexed oxygen uptake (14.9 mL/minper kg [IQR, 13.1–16.2]) versus controls (22.3 mL/min per kg [IQR, 16.9–27.6]; P=0.003) and COVIDnormal patients (19.1 mL/min per kg [IQR, 15.4–23.7]; P=0.04); (2) the lowest peak indexed cardiac output (4.7±1.2 L/min per m2) versus controls (6.0±1.2 L/min per m2; P=0.004) and COVIDnormal patients (5.7±1.5 L/min per m2; P=0.02), associated with lower indexed stroke volume (SVi:COVIDreduced 39±10 mL/min per m2 versus COVIDnormal 43±7 mL/min per m2 versus controls 48±10 mL/min per m2; P=0.02). There were no differences in peak tissue oxygen extraction or biventricular ejection fractions between groups. There were no associations between COVID‐19 illness severity and peak magnetic resonance–augmented cardiopulmonary exercise testing metrics. Peak indexed oxygen uptake, indexed cardiac output, and indexed stroke volume all correlated with duration from discharge to magnetic resonance–augmented cardiopulmonary exercise testing (P<0.05). Conclusions Magnetic resonance–augmented cardiopulmonary exercise testing suggests failure to augment stroke volume as a potential mechanism of exercise intolerance in previously hospitalized patients with COVID‐19. This is unrelated to disease severity and, reassuringly, improves with time from acute illness.